A New genus of flightless leafhoppers (Hemiptera: Cicadellidae: Megophthalminae) from the Páramo of Northern South America - Dietrich, Christopher H. (Zootaxa, 2022)
Diablophthalmus, gen. nov., is described and illustrated based on two new species, D. wygodzinskyorum sp. n., and D. marmoratus sp. n. from Páramo habitats in Colombia. These insects are the first recorded members of tribe Megophthalmini from South America. Morphologically convergent features shared with other soil-dwelling Membracoidea are discussed.